2009
DOI: 10.1016/j.jacc.2008.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physician Volume on the Relationship Between Hospital Volume and Mortality During Primary Angioplasty

Abstract: During primary PCI, physician experience significantly modifies the hospital volume-outcome relationship. Therefore, policymakers need to consider physician experience when developing strategies to improve access to primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 26 publications
1
99
1
1
Order By: Relevance
“…Any relationship between outcome and operator volume is probably minimized through careful case selection by operators themselves: the low volume, more risk averse, or limited skilled and experienced operators, likely and appropriately avoid high-risk elective cases. Supporting this point, there are excellent data that annual operator volume is highly predictive of outcomes in primary PCI for STEMI [47,48]. No studies have examined the impact of lifetime operator experience as a predictor of outcomes.…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…Any relationship between outcome and operator volume is probably minimized through careful case selection by operators themselves: the low volume, more risk averse, or limited skilled and experienced operators, likely and appropriately avoid high-risk elective cases. Supporting this point, there are excellent data that annual operator volume is highly predictive of outcomes in primary PCI for STEMI [47,48]. No studies have examined the impact of lifetime operator experience as a predictor of outcomes.…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…Among cardiovascular procedures, the inverse relationship between procedural volume and outcomes has been most consistently shown for coronary artery bypass surgery and percutaneous coronary interventions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Several studies have shown that higher physician volume of pacemaker implantations is associated with improved outcomes, [17][18][19][20][21] which suggests that a similar relationship may exist for implantable cardioverterdefibrillators (ICDs). The only prior study of this question analyzed Medicare claims of 9854 patients who received an initial ICD between 1999 and 2001 and showed that higher physician procedure volume was associated with fewer mechanical complications and infections, but not with death, within 90 days after ICD implantation.…”
mentioning
confidence: 99%
“…Notwithstanding these limitations, the general finding of the study-that low-volume operators and institutions are associated with poorer PCI outcomes-is consistent with previous literature. 13,14,16,19 One of the more sobering, albeit subtle, findings from this study was that the median operator PCI volume was 75 cases per year, with a substantial fraction of operators falling below 50 PCIs per year, a level that barely meets current ACCF/AHA/SCAI recommendations. Although these numbers may have underestimated true operator volume by excluding outpatient procedures as noted above, they nonetheless fall far below the optimal threshold of ≈300 per year identified in their study.…”
Section: Circulationmentioning
confidence: 67%
“…[13][14][15][16] As a result, minimum volume standards for those physicians performing PCI have been established by multiple professional societies. The 2011 American College of Cardiology Foundation/ American Heart Association/ Society for Cardiovascular Angiography and Interventions (ACCF/AHA/SCAI) clinical competence statement on PCI recommended that PCIs be performed only by operators with an annual volume of >75 procedures at hospitals with an annual volume of >400 procedures.…”
mentioning
confidence: 99%